Celiac Disease 30 Years After Diagnosis: Struggling With Gluten-free Adherence or Gaining Gluten Tolerance?. Issue 3 (September 2018) - Norsa, Lorenzo; Branchi, Federica; Bravo, Marianna; Ferretti, Francesca; Roncoroni, Leda; Somalvico, Francesco; Conte, Dario; Bardella, Maria Teresa; Fabiano, Sabrina; Barigelletti, Giulio; Elli, Luca
ABSTRACT: Objectives: Studies investigating patients with coeliac disease (CD) on very long-term follow-up are limited. We aimed to evaluate the characteristics of patients with CD diagnosed more than 30 years ago. Methods: Clinical, histologic, genetic, and demographic data of patients with CD diagnosis made before 1985 were collected and their standardised mortality ratio calculated. According to the gluten-free diet (GFD) status, CD patients were divided into 3 groups and a specific questionnaire on GFD awareness and gluten-free products was administered to patients and caregivers. Results: A total of 337 CD patients were included in the study. The standardised mortality ratio was 0.37 (confidence interval 0.10 to 0.94) compared with a matched population. A total of 197 patients were grouped according to GFD compliance, with 35 CD patients reporting chronic voluntary gluten ingestion. No significant differences were found between groups regarding family history of CD, symptoms and histology at diagnosis, autoimmune disorders. Follow-up histology was performed in 63 patients. Twenty patients had normal histology on gluten-containing diet (GCD). Questionnaire scores were lower in patients on GCD. Caregivers scores were not correlated with patients' gluten consumption. Conclusions: Although poor adherence to GFD is the major predictor of persistence of mucosal lesions at follow-up histology, a proportion of patients did not show a relapse of villous atrophy in spite chronic voluntary gluten ingestion, nor increase in mortality. Moreover, GFD knowledge and adherence could be partly lost during the transition between childhood and adulthood. Abstract : Supplemental Digital Content is available in the text